MIST: multiple instance learning network based on Swin Transformer for whole slide image classification of colorectal adenomas. Issue 2 (7th December 2022) - Cai, Hongbin; Feng, Xiaobing; Yin, Ruomeng; Zhao, Youcai; Guo, Lingchuan; Fan, Xiangshan; Liao, Jun
Abstract: Colorectal adenoma is a recognized precancerous lesion of colorectal cancer (CRC), and at least 80% of colorectal cancers are malignantly transformed from it. Therefore, it is essential to distinguish benign from malignant adenomas in the early screening of colorectal cancer. Many deep learning computational pathology studies based on whole slide images (WSIs) have been proposed. Most approaches require manual annotation of lesion regions on WSIs, which is time‐consuming and labor‐intensive. This study proposes a new approach, MIST – Multiple Instance learning network based on the Swin Transformer, which can accurately classify colorectal adenoma WSIs only with slide‐level labels. MIST uses the Swin Transformer as the backbone to extract features of images through self‐supervised contrastive learning and uses a dual‐stream multiple instance learning network to predict the class of slides. We trained and validated MIST on 666 WSIs collected from 480 colorectal adenoma patients in the Department of Pathology, The Affiliated Drum Tower Hospital of Nanjing University Medical School. These slides contained six common types of colorectal adenomas. The accuracy of external validation on 273 newly collected WSIs from Nanjing First Hospital was 0.784, which was superior to the existing methods and reached a level comparable to that of the local pathologist's accuracy of 0.806. Finally, we analyzed the interpretability of MIST and observed that the lesion areas of interest in MIST were generally consistent with those of interest to local pathologists. In conclusion, MIST is a low‐burden, interpretable, and effective approach that can be used in colorectal cancer screening and may lead to a potential reduction in the mortality of CRC patients by assisting clinicians in the decision‐making process. © 2022 The Pathological Society of Great Britain and Ireland.